University students dataset related to achievement, classroom practices, perceptions and attitudes of multimediabased learning quantum physics - Nyirahabimana, Pascasie; Minani, Evariste; Nduwingoma, Mathias; Kimeza, Imelda (F1000Research, 2023)
This dataset presents data collected to assess teaching and learning of quantum physics at the University of Rwanda - College of Education (UR-CE), Rwanda. Data were collected between August and November 2019 as the baseline, and between January and April 2022 under a quasi-experimental design. Three sets of data were collected. The first set was about students' performance and conceptual understanding collected before and after teaching intervention (lecture method or multimedia-aided approach) using mainly Quantum Physics Conceptual Survey (QPCS). The second set documented classroom practices during teaching and learning using the Classroom Observation Protocol for Undergraduate STEM (COPUS). The last set is comprised of the data related to lecturers' and students' perceptions before teaching and learning quantum physics and students' attitudes after learning Quantum physics. The Quantum Physics Attitude Test (QPAT) was mainly used to collect these data. The dataset is important to education stakeholders because university managers can visualize the status of teaching and learning outcomes, lecturers can reflect on the study, and researchers can use the data to analyze various independent variables.
Keywords: Dataset; Conceptual understanding; Rwanda; Student academic achievement; Student attitude; Quantum mechanics; Quantum physics; University students